Cryo‐EM structure of fatty acid synthase (FAS) from Rhodosporidium toruloides provides insights into the evolutionary development of fungal FAS. (2nd April 2015) - Fischer, Manuel; Rhinow, Daniel; Zhu, Zhiwei; Mills, Deryck J.; Zhao, Zongbao K.; Vonck, Janet; Grininger, Martin
Abstract Fungal fatty acid synthases Type I (FAS I) are up to 2.7 MDa large molecular machines composed of large multifunctional polypeptides. Half of the amino acids in fungal FAS I are involved in structural elements that are responsible for scaffolding the elaborate barrel‐shaped architecture and turning fungal FAS I into highly efficient de novo producers of fatty acids. Rhodosporidium toruloides is an oleaginous fungal species and renowned for its robust conversion of carbohydrates into lipids to over 70% of its dry cell weight. Here, we use cryo‐EM to determine a 7.8‐Å reconstruction of its FAS I that reveals unexpected features; its novel form of splitting the multifunctional polypeptide chain into the two subunits α and β, and its duplicated ACP domains. We show that the specific distribution into α and β occurs by splitting at one of many possible sites that can be accepted by fungal FAS I. While, therefore, the specific distribution in α and β chains in R. toruloides FAS I is not correlated to increased protein activities, we also show that the duplication of ACP is an evolutionary late event and argue that duplication is beneficial for the lipid overproduction phenotype.